Peningkatan Pengetahuan dan Keterampilan Peternak Melalui Pembuatan Silase Sebagai Sumber Pakan Ternak Domba Garut di Desa Penancangan Kota Serang - silda, Regis; Musaqopul Fikri; Rafif Gusti Wicaksono; Fulvian Prima Benedicta; Galang Akbar Ramadhan; Tata Hardiansyah; Ulfa Nurrofingah; Magfira; Tuti Puspita Sari; Yunia Deva Istikhodriah (LOSARI DIGITAL, 2025)
This community service activity addresses the issue of limited forage availability during the dry season faced by sheep farmers in Penancangan Village, Serang City. The focus of the program is to enhance farmers’ knowledge and skills through training on silage production as an alternative and sustainable feed source. The purpose of this activity is to improve farmers’ capacity to manage feed efficiently, independently, and economically. The implementation method was educational and applicative, involving socialization, demonstrations, and hands-on practice in producing silage using local materials such as alang-alang grass, rice bran, molasses, and EM4. The results showed a 100% increase in participants’ knowledge across all indicators related to silage and feed processing. Farmers were able to independently produce silage, contributing to improved livestock productivity and the sustainability of small- scale livestock enterprises in Penancangan Village.